Perbedaan Nilai Apgar antara Kelahiran Pervaginam dan Kelahiran Seksio Sesarea pada Partus Macet - Rizky Mas'ah; Tri Budi Wiryanto; . Sumardiyono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Labour is considered obstructed when the presenting part of the fetus cannot progress into the birth canal, despite strong uterine contractions. Obstructed labour can leading fetal asphyxia that indicate low APGAR score. In this case the delivery method can affect the state of the fetus. This study aimed to determine the difference APGAR score between vaginal delivery and caesarean section in obstructed labour. Methods: This analytic study was observational using cross sectional approach. The population of this study was all infants who was born by mother with vaginal delivery and caesarean section deliveries in obstructed labor at RSUD Dr. Moewardi. A total of 30 subjects were selected by purposive sampling method in accordance with the inclusion criteria. The data of APGAR score was collected by viewing the medical records from the subject. The data was analyzed using Independent T Test on SPSS 16.0 for Windows program. Results: The analysis showed a difference between APGAR score (first and fifth minute) in each group was significant. The first minute APGAR score has p 0.021 obtained for delivery method. APGAR score at five minute has p 0.041 obtained for delivery method. APGAR score at ten-minute was not significant with the delivery method, with a p-value 0.059. Conclusions: There is statistically significant differences between APGAR score at first and fifth minute in vaginal delivery and caesarean section in obstructed labor. Keywords: apgar score,obstructed labour,delivery.